2002
DOI: 10.1177/107780102400447087
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents at Work

Abstract: This study describes adolescents' experiences with sexual harassment while working part-time and attending high school. In a sample of 712 high school students, 35% of the 332 students who work part-time report experiencing sexual harassment (63% girls, 37% boys). Results revealed that there are differences in the experience of sexual harassment by gender, work relationship, and emotional reaction. Students experienced harassment from supervisors (19%), coworkers (61%), and unidentified others at work (18%). G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 21 publications
3
13
0
2
Order By: Relevance
“…Investigations among U.S. samples support this idea. For instance, Fineran (2002) offered evidence that female adolescents were more upset than their male counterparts by unwanted sexual attention at work, suggesting a gender difference in the appraisal of sexual harassment. We therefore developed the next hypothesis as follows:…”
Section: Appraisal Of Sexually Harassing Eventsmentioning
confidence: 97%
See 1 more Smart Citation
“…Investigations among U.S. samples support this idea. For instance, Fineran (2002) offered evidence that female adolescents were more upset than their male counterparts by unwanted sexual attention at work, suggesting a gender difference in the appraisal of sexual harassment. We therefore developed the next hypothesis as follows:…”
Section: Appraisal Of Sexually Harassing Eventsmentioning
confidence: 97%
“…Yet, despite this body of scholarship on work stressors, that literature has virtually overlooked the ripe conditions for the sexualized exploitation of adolescents in their early work experience. One exception to this paucity of attention was a study by Fineran (2002), which offered some descriptive information about patterns among adolescent encounters with sexual harassment. Surveying U.S. highschool-age boys and girls who worked part-time, she reported that 63% of the girls had experienced some form of sexual harassment at work, and 37% of the boys reported the same.…”
Section: Adolescent Workforce Participationmentioning
confidence: 97%
“…The organizational and management literature addresses gender differences in different aspects of job performance (Mausner-Dorsch & Eaton, 2000), and the mental health literature explores marital and individual differences between working and non-working females (described in previous two paragraphs). In addition, a couple of articles in violence-specific journals look at sexual harassment (Campbell, Raja, & Grining, 1999;Fineran, 2002). Buckley (2002) was the only author found who addressed clinical work with professional women.…”
Section: Therapy With Women In the Workplacementioning
confidence: 98%
“…People commonly express components of sexuality and power through sexual harassment. Negative effects of harassment include decreased self-confidence, anger, anxiety, depression, helplessness, fear of rape and crime (Fineran, 2002). It is estimated that at least one-half of all US women and 15 percent of men will be sexually harassed at some point in their careers (Bell et al, 2002).…”
Section: Sexual Harassmentmentioning
confidence: 98%
See 1 more Smart Citation